STUDI ANALISIS POTENSI SUMBER MATA AIR UNTUK MEMENUHI KEBUTUHAN AIR MASYARAKAT KECAMATAN CISAYONG KABUPATEN TASIKMALAYA - Pahrezi Sepyan, Aqmal; Nurmayadi, Dicky (JITSi : Jurnal Ilmiah Teknik Sipil, 2023)
Abstract Spring water is one of the water sources used by the community to supply their daily water requirement, such as in Cipeteuy Village, Sukamukti Village, Cisayong District, local people use Cipeteuy Spring sources to supply their water requirement. Cipeteuy Spring Source is expected to be used for the water requirement of the people of Cisayong District every year. Therefore, this study was conducted to review the availability of water and the carrying capacity of Cipeteuy Spring, Sukamukti Village to supply the water requirement of the people of Cisayong District in 2028. Water availability was calculated using the NRECA Model method and calibrated with the NSE model from the results of daily observations at the study site. With the availability of Cipeteuy Spring water with the amount of discharge each month from January to December is 82,218,240 liters, 109,252,800 liters, 113,322,240 liters, 109,978,560 liters, 93,648,960 liters, 75,660,480 liters, 62,259,840 liters, 49,066,560 liters, 44,167,680 liters, 49,455,360 liters, 86,106,240 liters, and 96,163,200 liters, after analyzing the carrying capacity of Cipeteuy Spring discharge waterunable to meet the water needs of the people of Cisayong District by 2028. Keywords: spring, water requirement, NRECA model, water carrying capacity Abstrak Mata air merupakan salah satu sumber air yang digunakan masyarakat untuk memenuhi kebutuhan air sehari – hari, seperti di Kampung Cipeteuy Desa Sukamukti Kecamatan Cisayong masyarakat setempat memanfaatkan sumber Mata Air Cipeteuy untuk memenuhi kebutuhan airnya. Sumber Mata Air Cipeteuy diharapkan dapat digunakan untuk kebutuhan air masyarakat Kecamatan Cisayong setiap tahun. Maka dari itu penelitian ini dilakukan untuk meninjau ketersediaan air dan daya dukung Mata Air Cipeteuy Desa Sukamukti untuk memenuhi kebutuhan air masyarakat Kecamatan Cisayong pada tahun 2028. Ketersediaan air dihitung menggunakan metode Model NRECA dan di kalibrasi dengan model NSE dari hasi pengamatan harian di lokasi penelitian. Dengan ketersediaan air Mata Air Cipeteuy dengan jumlah debit setiap bulannya dari bulan Januari hingga Desember adalah 82.218.240 liter, 109.252.800 liter, 113.322.240 liter, 109.978.560 liter, 93.648.960 liter, 75.660.480 liter, 62.259.840 liter, 49.066.560 liter, 44.167.680 liter, 49.455.360 liter, 86.106.240 liter, dan 96.163.200 liter, setelah dilakukan analisis daya dukung air debit Mata Air Cipeteuy tidak dapat memenuhi kebutuhan air masyarakat Kecamatan Cisayong pada tahun 2028. Kata kunci: mata air, kebutuhan air, Model NRECA, daya dukung air.